Specific shoot formation in Miscanthus sacchariflorus (Poaceae) under different environmental factors and DNA passportization using ISSR markers - O. V. Dorogina; N. S. Nuzhdina; G. A. Zueva; Yu. A. Gismatulina; O. Yu. Vasilyeva (Вавиловский журнал генетики и селекции)
The generic complex Miscanthus Anderss. (Poaceae) is a unique example among herbaceous plants characterized by high values of growth of aboveground vegetative mass and practical use as a valuable source of alternative energy. Miscanthus is one of the most efficient solar energy accumulators, and since phytomeliorative use implies the cultivation of these resource plants in inconvenient and semi-shady areas, the question about the effect of insufficient lighting on the productivity of Miscanthus arises. As a result of a long-lasing introduction effort, the Central Siberian Botanical Garden SB RAS created a population of Miscanthus sacchariflorus (Maxim.) Benth., which has good prospects for growing under the conditions of the forest-steppe area in Western Siberia. The goals of our study were: (1) to determine the peculiarities of shoot formation, (2) to assess the cellulose and lignin accumulation in M. sacchariflorus populations under different lighting conditions and (3) to perform a DNA passportization of the Miscanthus population by ISSR marking. Evaluation of shoot formation and the amount of accumulated cellulose and lignin in plants was carried out under different degrees of illumination: one variant was grown in a sunny area, and the other, in partial shade. As a result of analysis of variance, it was found that the number of shoots does not depend on environmental conditions, but on the age of the plant, while environmental conditions have a significant effect on plant height. Although the samples of both M. sacchariflorus variants were characterized by different rates of creation of a continuous projective cover, plants in semi-shaded areas formed up to 89.34 % of shoots compared to their peers in illuminated areas, which did not affect significantly the size of the aboveground mass and the cellulose content in it. As a result of ISSR-analysis of genomic DNA in the M. sacchariflorus population, unique molecular polymorphic fragments were identified, which can be used for identification and DNA passportization at the inter-population level. Thus, the complex use of M. sacchariflorus as a valuable meliorative and bioenergetic culture is due to the high adaptive potential of this species. It was found that the illumination factor has virtually no effect on the amount of the cellulose content in the shoot, and a reduced content of the technologically undesirable lignin was observed in plants growing in the partial shade conditions.